Halal Certification and Product Rebranding: A Strategy to Increase Sales at the Halal Chicken Soto Center of Tamanan, Kediri - Sutantri Sutantri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study presents a comprehensive analysis of the synergistic impact of halal certification and product rebranding efforts on increasing sales at the Halal Chicken Soto Center of Tamanan, Kediri. Using a case study approach, the research examines how the implementation of halal certification—initially perceived as a form of religious compliance and consumer protection—has evolved into a strategic competitive advantage. When combined with rebranding initiatives, including visual improvements and enhanced communication, halal status becomes an attractive value proposition for consumers. The findings indicate that the integration of these two strategies not only strengthens consumer trust and expands market reach but also makes a tangible contribution to increased sales. This demonstrates that for culinary Micro, Small, and Medium Enterprises (MSMEs), halal certification supported by effective rebranding can serve as a strategic approach to optimizing sales growth potential, while simultaneously contributing to the development of Indonesia’s Islamic economic ecosystem.